Assessment of Fatigue and Recovery in Male and Female Athletes After 6 Days of Intensified Strength Training. Issue 12 (December 2016) - Raeder, Christian; Wiewelhove, Thimo; Simola, Rauno Álvaro De Paula; Kellmann, Michael; Meyer, Tim; Pfeiffer, Mark; Ferrauti, Alexander
Abstract : Abstract: Raeder, C, Wiewelhove, T, Simola, RÁDP, Kellmann, M, Meyer, T, Pfeiffer, M, and Ferrauti, A. Assessment of fatigue and recovery in male and female athletes after 6 days of intensified strength training. J Strength Cond Res 30(12): 3412–3427, 2016—This study aimed to analyze changes of neuromuscular, physiological, and perceptual markers for routine assessment of fatigue and recovery in high-resistance strength training. Fourteen male and 9 female athletes participated in a 6-day intensified strength training microcycle (STM) designed to purposefully overreach. Maximal dynamic strength (estimated 1 repetition maximum [1RMest ]; criterion measure of fatigue and recovery); maximal voluntary isometric strength (MVIC); countermovement jump (CMJ) height; multiple rebound jump (MRJ) height; jump efficiency (reactive strength index, RSI); muscle contractile properties using tensiomyography including muscle displacement (Dm), delay time (Td), contraction time (Tc), and contraction velocity (V90); serum concentration of creatine kinase (CK); perceived muscle soreness (delayed-onset muscle soreness, DOMS) and perceived recovery (physical performance capability, PPC); and stress (MS) were measured before and after the STM and after 3 days of recovery. After completing the STM, there were significant ( p ⩽ 0.05) performance decreases in 1RMest (%[INCREMENT] ± 90% confidence limits, ES = effect size; −7.5 ± 3.5, ES = −0.21), MVIC (−8.2 ± 4.9, ES = −0.24), CMJ (−6.4 ± 2.1, ES = −0.34), MRJ (−10.5 ± 3.3, ES = −0.66), and RSI (−11.2 ± 3.8, ES = −0.73), as well as significantly reduced muscle contractile properties (Dm, −14.5 ± 5.3, ES = −0.60; V90, −15.5 ± 4.9, ES = −0.62). After days of recovery, a significant return to baseline values could be observed in 1RMest (4.3 ± 2.8, ES = 0.12), CMJ (5.2 ± 2.2, ES = 0.28), and MRJ (4.9 ± 3.8, ES = 0.32), whereas RSI (−7.9 ± 4.5, ES = −0.50), Dm (−14.7 ± 4.8, ES = −0.61), and V90 (−15.3 ± 4.7, ES = −0.66) remained significantly reduced. The STM also induced significant changes of large practical relevance in CK, DOMS, PPC, and MS before to after training and after the recovery period. The markers Td and Tc remained unaffected throughout the STM. Moreover, the accuracy of selected markers for assessment of fatigue and recovery in relation to 1RMest derived from a contingency table was inadequate. Correlational analyses also revealed no significant relationships between changes in 1RMest and all analyzed markers. In conclusion, mean changes of performance markers and CK, DOMS, PPC, and MS may be attributed to STM-induced fatigue and subsequent recovery. However, given the insufficient accuracy of markers for differentiation between fatigue and recovery, their potential applicability needs to be confirmed at the individual level.